2009
DOI: 10.1515/cclm.2009.153
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency testing project for brain natriuretic peptide (BNP) and the N-terminal part of the propeptide of BNP (NT-proBNP) immunoassays: the CardioOrmocheck study

Abstract: Background: We organized and conducted a proficiency testing study (CardioOrmocheck) to evaluate the differences in analytical performance of brain natriuretic peptide (BNP) and N-terminal proBNP (NTproBNP) immunoassays. Results: The mean total variability for BNP (50.6 %CV) was significantly higher than that for NT-proBNP (8.4 %CV). In addition, the mean variability due to differences between-methods (46.4 %CV) comprised the majority of the total variability for BNP. Betweenmethod variability for BNP compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 18 publications
5
72
0
Order By: Relevance
“…There are only minor differences between the commercial NTproBNP assays with variation across methods that is Ͻ10%. Despite this standardization, however, assay harmonization remains incomplete (32 ). The International Collaborative of NT-proBNP Study involving 1256 patients proposed a cutoff value for NT-proBNP assays below or above 125 ng/L.…”
Section: Nt-probnp Assaysmentioning
confidence: 99%
“…There are only minor differences between the commercial NTproBNP assays with variation across methods that is Ͻ10%. Despite this standardization, however, assay harmonization remains incomplete (32 ). The International Collaborative of NT-proBNP Study involving 1256 patients proposed a cutoff value for NT-proBNP assays below or above 125 ng/L.…”
Section: Nt-probnp Assaysmentioning
confidence: 99%
“…NT-proBNP is more stable in vivo and in vitro: it has a higher molecular mass and a longer biological plasma half-live and a lower intra-individual biological variation (Table 1). Furthermore, data from external quality assessment studies demonstrated that immunoassays methods for NT-proBNP share on average better analytical performances (including better sensitivity and imprecision) than those of BNP [1][2][3][4]. Furthermore, these studies also reported that there are large systematic differences (up to twofolds) between the BNP values measured by the most popular immunoassay methods, whereas the NT-proBNP methods show a between-method variability lower than 20% because they use calibrators and materials from the same manufacturer [3,4].…”
Section: Analytical Characteristics Of Bnp and Nt-probnp Methodsmentioning
confidence: 99%
“…Furthermore, data from external quality assessment studies demonstrated that immunoassays methods for NT-proBNP share on average better analytical performances (including better sensitivity and imprecision) than those of BNP [1][2][3][4]. Furthermore, these studies also reported that there are large systematic differences (up to twofolds) between the BNP values measured by the most popular immunoassay methods, whereas the NT-proBNP methods show a between-method variability lower than 20% because they use calibrators and materials from the same manufacturer [3,4]. Finally, from a clinical point of view, the circulating levels of NT-proBNP show a greater and progressive increment (on average, more than 120-folds compared to healthy subjects) from early to more severe disease in patients with heart failure (HF), as assessed by NYHA functional class, than those of BNP (i.e.…”
Section: Analytical Characteristics Of Bnp and Nt-probnp Methodsmentioning
confidence: 99%
See 2 more Smart Citations